Integrated Approach to Sensitize Medical Students on Management of Tobacco and Alcohol Use Disorders - Muralidhar M Kulkarni; George P Jacob; Sreejayan K; Samir Kumar Praharaj; Thippeswamy V; Veena G Kamath (Medsci Publications, 2016)
Introduction: The problem of tobacco and alcohol use disorders need to be addressed in a more effective manner than at present. The objectives of the study are to sensitise medical students regarding this problem, to impart them basic training to counsel the patients and to understand their perspective on this method of teaching. Methods: The Departments of Community Medicine and Psychiatry jointly conducted sessions for the third year medical students attending Community Medicine postings to sensitize them on tobacco and alcohol use disorders. Didactic lectures by the faculty and role plays by the students were followed by feedback by the faculty regarding basic counselling principles. A cross-sectional study using self-administered anonymous questionnaires, was conducted among these students. Results: Of the 175 questionnaires analysed, 95.4% agreed that medical students have to be sensitized about the problem of tobacco and alcohol use. 97.7% felt that they should acquire skills to identify persons with these disorders and 98.9% said that they needed training to counsel. Conclusion: Such interactive sessions in Community Medicine teaching will make the students comprehend better and make the learning more interesting. They will be better empowered to act at primary and secondary levels of prevention of substance use disorders.